Evaluating the differential effectiveness of social influence and personality-targeted alcohol prevention on mental health outcomes among high-risk youth: A novel cluster randomised controlled factorial design trial. (March 2020) - Newton, Nicola C; Stapinski, Lexine; Teesson, Maree; Slade, Tim; Champion, Katrina E; Barrett, Emma L; Birrell, Louise; Kelly, Erin; Mather, Marius; Conrod, Patricia J
Objective: This study examined the secondary mental health outcomes of two contrasting alcohol prevention approaches, whereby one intervention targets common underlying personality risk for alcohol use and mental health problems ( Preventure ) and the other targets alcohol- and drug-related behaviours and cognitions ( Climate Schools ). Methods: A 2 × 2 cluster randomised controlled factorial design trial was conducted in 26 Australian schools randomised to the following 4 conditions: Climate Schools ( n  = 6), Preventure ( n  = 7), combined Climate Schools and Preventure (CAP; n  = 6) or treatment as usual (TAU; n  = 7). Participants completed questionnaires at baseline, 6, 12, 24 and 36 months post-baseline including the Brief Symptom Inventory anxiety and depression scales and hyperactivity and conduct scales of the Strengths and Difficulties Questionnaire. Analyses focused on students who were at high-risk based on personality traits ( n  = 947; Mage  = 13.3). The effectiveness of each approach in reducing symptoms of internalising and externalising problems was assessed using multi-level mixed effects analysis. Results: Main effects for each intervention relative to not receiving that intervention revealed significant main effects of Preventure in reducing anxiety symptoms ( d  = −0.27, 95% confidence interval [CI] = [−0.53, −0.01], p  < 0.05) and a marginal effect in reducing depressive symptoms ( d  = −0.24, 95% CI = [−0.49, 0.01], p  = 0.06) over 3 years. Interaction effects revealed that when delivered alone, Preventure significantly reduced conduct problems ( d  = −0.45, 95% CI = [−0.78, −0.11], p  < 0.05) and hyperactivity symptoms ( d  = −0.38, 95% CI = [−0.70, −0.07], p  < 0.05) compared to TAU. Conclusion: This study is the first to report the effectiveness of personality-targeted alcohol prevention in reducing internalising and externalising symptoms relative to an active control, providing evidence in favour of its specificity in preventing concurrent substance use and mental health problems among high-risk youth.